Land pooling in Nepal from planned urban islands to city transformation. - Faust, Amy (Metro Manila, Philippines Asian Development Bank, 2020)
This paper assesses the outcomes of land pooling projects in Nepal and draws on examples from other Asian countries for a better understanding of how institutional capacities for land pooling vary and evolve.Global examples show that land pooling can transform entire cities, but the impact of decades-long experiences in Nepal have been limited. In the paper, policy and technical recommendations aim to mitigate bottlenecks and enhance successes learned from past experiences in Nepal and other countries. It also advises how Nepal can successfully implement more ambitious large-scale land pooling projects. This is the first in a series of three working papers that ADBs South Asia Urban Development and Water Division has produced to take a deeper look at the effectiveness and prospects of land pooling in developing country cities.
Keywords: Land use, Urban -- Nepal; Land use, Urban -- Environmental aspects; Agriculture -- Economic aspects -- South Asia,Nepal; Electronic books